2015
DOI: 10.1002/2014jd022602
|View full text |Cite
|
Sign up to set email alerts
|

The summer 2012 Greenland heat wave: In situ and remote sensing observations of water vapor isotopic composition during an atmospheric river event

Abstract: During 7–12 July 2012, extreme moist and warm conditions occurred over Greenland, leading to widespread surface melt. To investigate the physical processes during the atmospheric moisture transport of this event, we study the water vapor isotopic composition using surface in situ observations in Bermuda Island, South Greenland coast (Ivittuut), and northwest Greenland ice sheet (NEEM), as well as remote sensing observations (Infrared Atmospheric Sounding Interferometer (IASI) instrument on board MetOp‐A), depi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 60 publications
2
110
1
Order By: Relevance
“…2). Recent monitoring data have revealed that (i) deuterium excess is low for subtropical Atlantic vapour and high for vapour formed at the Arctic sea-ice margin, where high kinetic fractionation occurs due to low relative humidity, and (ii) this vapour deuterium excess is preserved during transportation towards Greenland (Jouzel et al, 2013;Bonne et al, 2015). Higher deuterium excess recorded during GS (Masson-Delmotte et al, 2005) may reflect enhanced contribution of moisture from the Nordic Seas towards Greenland (as also previously suggested for Heinrich stadial 4 interval; Wary et al, 2016), when the Norwegian Sea appears relatively warm and surrounded by sea-ice-covered areas (providing low humidity air masses), while the North Atlantic surface is cold and marked by large sea-ice expansion (Hillaire-Marcel and de Vernal, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…2). Recent monitoring data have revealed that (i) deuterium excess is low for subtropical Atlantic vapour and high for vapour formed at the Arctic sea-ice margin, where high kinetic fractionation occurs due to low relative humidity, and (ii) this vapour deuterium excess is preserved during transportation towards Greenland (Jouzel et al, 2013;Bonne et al, 2015). Higher deuterium excess recorded during GS (Masson-Delmotte et al, 2005) may reflect enhanced contribution of moisture from the Nordic Seas towards Greenland (as also previously suggested for Heinrich stadial 4 interval; Wary et al, 2016), when the Norwegian Sea appears relatively warm and surrounded by sea-ice-covered areas (providing low humidity air masses), while the North Atlantic surface is cold and marked by large sea-ice expansion (Hillaire-Marcel and de Vernal, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…These two periods were associated with passages of strong precipitation events, so-called atmospheric river (AR): poleward moisture was organized in a filamentary structure stretching from subtropical latitudes to Antarctica, leading to heavy snow accumulation events over DML (Gorodetskaya et al 2014). Note that, in Greenland, an AR event was observed in summer 2012 (e.g., Neff et al 2014), including water vapor isotope monitoring (Bonne et al 2015), and let to widespread melt at the ice sheet surface (Nghiem et al 2012). As observed over the Greenland ice sheet, T max rose at Syowa above the melting point during these events.…”
Section: Methodsmentioning
confidence: 99%
“…Neff et al (2014) examined synoptic-scale atmospheric conditions over the GrIS during July 2012 from various aspects and summarized notable features as follows: (1) warm air originating from a record North American heat wave (the North American drought of 2012 was the worst since 1895), (2) transitions in the Arctic Oscillation, (3) transport of water vapor via an atmospheric river over the Atlantic to Greenland, and (4) the presence of warm ocean waters south of Greenland. Bonne et al (2015) clearly showed that moist air mass was advected northward following a narrow band reaching southern Greenland and then it moved northward along the western Greenland coast around 9 July. Observed features of above-mentioned meteorological properties during the IOP at the SIGMA-A site are consistent with these large-scale atmospheric conditions.…”
Section: Meteorological Observationsmentioning
confidence: 99%